2023
DOI: 10.3390/insects14090735
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Toxicity of Four Essential Oils, Their Predominant Constituents, Their Mixtures against Varroa Mite, and Their Selectivity to Honey Bees (Apis cerana and A. mellifera)

Tekalign Begna,
Delgermaa Ulziibayar,
Daniel Bisrat
et al.

Abstract: The honey bee (Apis mellifera) faces a significant threat from Varroa destructor, causing the losses of millions of colonies worldwide. While synthetic acaricides are widely used to control Varroa infestations, excessive application has led to resistant strains and poses side effects on the host. Consequently, there is an urgent need for a new acaricide that is both effective and affordable, yet safe to use on bees. One potential source of these acaricides is essential oils (EOs) and their constituents. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The essential oil extracted from Thymus schimperi Ronniger exhibited selective toxicity against V. destructor, approximately 91 times higher than that necessary for Apis mellifera and 27 times higher than for Apis cerana Fabricius [67]. In contrast, the main component of the essential oil, thymol, when tested in its pure form, showed selective toxicity of only 6.5 against A. mellifera and 4.4 against A. cerana.…”
mentioning
confidence: 86%
“…The essential oil extracted from Thymus schimperi Ronniger exhibited selective toxicity against V. destructor, approximately 91 times higher than that necessary for Apis mellifera and 27 times higher than for Apis cerana Fabricius [67]. In contrast, the main component of the essential oil, thymol, when tested in its pure form, showed selective toxicity of only 6.5 against A. mellifera and 4.4 against A. cerana.…”
mentioning
confidence: 86%
“…The safety of EOs on A . mellifera is documented in the literature [ 38 40 ]. However, we did not investigate the toxicity of our treatments on bees.…”
Section: Discussionmentioning
confidence: 99%
“…The small group size of our study may have limited our findings. Many field studies have shown that several EOs and their main components (such as thymol and carvacrol) are effective in controlling Varroa mites under laboratory conditions [40][41][42]. Oregano and cinnamon EOs showed a high level of mite toxicity and a low level of bee toxicity in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…These results should be assessed in further tests since Taha et al (2020) stated that using garlic oil decreased varroa mites numbers by 90%, this disagrees with the results of this experiment, where the effects of garlic oil reduced the number of the mites by only 72% and were not superior as they mentioned; however, the results of this assessment were agreed with what Faraj et al (2021) found. A mixture of two or more essential oils extracted from plant material could lead to a reduction of varroa mites damage, where Begna et al (2023) claimed that mixing some essential oils, a 1:1 mixture of thymol and carvacrol, decreased the number of V. destructor , rather than using single oil. The agreement of the results of the second experiment with the results obtained from the initial test confirms the possibility of benefiting from these materials in controlling varroa mites.…”
Section: Discussionmentioning
confidence: 99%